2022
DOI: 10.1002/smll.202203702
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Number of Electron Reservoirs in Nonporous, High‐Conducting Coordination Polymers CuxBHT (x = 3, 4, and 5, BHT = Benzenehexathiol) for Improved Faradaic Capacitance

Abstract: Although asymmetric supercapacitors (ASCs) can achieve high energy density, the lifespan and power density are severely suppressed due to the low conductivity of using pseudocapacitive or battery‐type electrode materials. Recently, nonporous conductive coordination polymers (c‐CPs) have sparked interests in supercapacitors. However, their performance is expected to be limited by the nonporous features, low specific surface area and absence of ion‐diffusion channels. Here, it is demonstrated that the capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The slow component is ascribed to the nonradiative recombination of the dark STEs, which should be responsible for the nonemission at ambient conditions. At 7.5 GPa, the lifetime of two fast components was prolonged (τ 1 ≈6.53 ps and τ 2 ≈115.42 ps) compared to its initial state due to the deepening of the defect state and the increase of defect density under high pressure [17] . The slow component of τ 3 ≈3.73 ns is assigned to the emissive decay of the bright STEs, corresponding to the efficient broadband emission and the long‐lived process of TRPL [14b, 18] .…”
Section: Resultsmentioning
confidence: 95%
“…The slow component is ascribed to the nonradiative recombination of the dark STEs, which should be responsible for the nonemission at ambient conditions. At 7.5 GPa, the lifetime of two fast components was prolonged (τ 1 ≈6.53 ps and τ 2 ≈115.42 ps) compared to its initial state due to the deepening of the defect state and the increase of defect density under high pressure [17] . The slow component of τ 3 ≈3.73 ns is assigned to the emissive decay of the bright STEs, corresponding to the efficient broadband emission and the long‐lived process of TRPL [14b, 18] .…”
Section: Resultsmentioning
confidence: 95%
“…It is worth noting that the M-dithiolene units consisting of planar tetra-coordinated Ag/Cu atoms with the benzene rings and the extended Ag–S networks can be deemed as the faradaic redox sites. 27,37,38 Overall, the well-defined layered structures of Ag 5 BHT and CuAg 4 BHT and their high electrical conductivities and hydrolytic stabilities as well as dense redox sites stimulated us to evaluate their performance in electrochemical capacitors.…”
Section: Resultsmentioning
confidence: 99%
“…15,23,24 Recent studies have demonstrated that the faradaic redox processes are commonly not limited by solid-state ion diffusion and that the energy storage capacity of nonporous c-CPs is mainly related to the built-in redox sites in their structure. 25–27 Remarkably, the introduction of heterometallic atoms in c-CPs can regulate their electronic structures, redox activities, morphologies, and enhance the charge transfer between different metal sites, which has emerged as an attractive tactic for lowering the kinetic energy barrier of the electrochemical processes. 28–31 For instance, Co–Ni, Co–Zn, and Fe–Co MOFs have been developed as efficient pseudocapacitive or battery-type electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…This further confirms the importance of A-CuBHT for improving the capacitance performance of hybrid materials. Here, we assume that the main reasons for the improvement of the performance of hybrid materials are the excellent charge storage capacity of A-CuBHT and the synergistic effect between MoS 2 and A-CuBHT, namely, the possible existence of Cu plane fourcoordination structure units in A-CuBHT can store charges (Figure S6), 34 which creates conditions for the improvement of the performance of hybrid materials. Second, MoS 2 nanosheets can provide a large number of attachment sites for the formation of A-CuBHT, resulting in more redox-active sites of A-CuBHT exposed in the electrolyte.…”
Section: Electrochemical Characterization Of 1t(h) Phase Mos 2 A-cub...mentioning
confidence: 99%
“…To the best of our knowledge, the research on metal−organic coordination polymers and MoS 2 hybrid materials in the field of electrochemical energy storage is still very rare. Here, amorphous Cu 3 BHT (A-CuBHT), which is an amorphous form of metal− organic coordination polymer Cu 3 BHT with high conductivity 33 and high electrochemical energy storage capacity, 34 is used to hybridize with MoS 2 to improve its performance. The results indicate that hybridizing of A-CuBHT and the prepared 1T(H) phase MoS 2 with a 1T phase concentration of 76.6% at a proper weight ratio can effectively improve the conductivity of the hybrids and stabilize 1T phase MoS 2 , resulting in a significant increase in the rate performance and capacitance of the electrode based on this hybrid material.…”
Section: Introductionmentioning
confidence: 99%